(untitled) (Educational Dimension, 2020)
An increasing number of countries are recognising the importance of financial literacy, and have included financial education in school curricula. Support for the implementation of financial education can be viewed by the main public, private and civic organizations a critical long-term investment in human capital. The issue of financial literacy is defined in the main state documents of Ukraine. The introduction of digital technologies has opened wide opportunities for their use in the field of financial education, they increase motivation to learn, stimulate students’ cognitive interest and increase the efficiency of independent work. The issue of financial literacy is defined in the main basic documents of Ukraine, such as the Law of Ukraine "On Education" and "State Standard of Basic Secondary Education" (2020), in which entrepreneurship and financial literacy are key competencies. The aim of the article is to analyze the European experience in the formation of financial literacy in a digital learning environment in the context of reforming domestic education. To achieve this goal, a set of research methods was used: analysis and systematization of scientific literature, works of domestic and foreign authors; comparative and pedagogical analysis, which is used to compare and generalize different views on the organization of financial education in schools of the European Union. The article is considered the objectives and key components of the Core Competencies Framework on Financial Literacy for Youth developed by the OECD International Network on Financial Education (OECD/INFE) and presents the framework of core competencies. The results of the international study of the quality of education PISA-2018 on the assessment of financial literacy are considered. The experience of European countries in creating and using a digital learning environment for the effective implementation of financial education: portals, websites, games, etc. is considered and analyzed.